Effectiveness of the 12-step program among addicts' codependents in Iran - Ajri, Zahra (2010)
This study aims to find the effectiveness of the 12-step program among codependents in Iran. Specifically, this study attempted to determine the changes in three variables, namely the spiritual aspect, relationship with others and self-care, between the experimental practitioners and control non-practitioners groups. This research focused on the main characteristics of codependency in order to investigate the effectiveness of the 12-step program in assisting family members of addicts/alcoholics to recover from codependency. This study was divided into three stages. First, the differences between the experimental and control groups, each consisted of 30 individuals, in the three variables mentioned above were investigated. Second, in order to show the process of recovery within the experimental group, the differences in the three variables between before and after practicing the 12-step program were investigated. Third, to better understand the recovery tools, family activities at Al-Anon/Nar-Anon participated by the experimental group were measured. This study employed causal-comparative design in order to achieve the research objectives and the instrument was a self-administered questionnaire. The theory of empowerment is the key theory in conducting this research. The 12-step program focuses on twelve steps that help families or relatives of addict/alcoholics to recover from codependency. The main concept in this program is spirituality. All principles in the 12-step program guide families to have spiritual,peaceful and healthy lives. Al-Anon and Nar-Anon are two groups which offer such program to families of alcoholics and addicts. The findings of this study showed that there were significant differences between the experimental and control groups in the three variables namely spirituality, relationship with others and self-care. Independent sample t-test revealed that family of addicts who practice the 12-step program showed low codependency symptoms compared to non-practitioners. Additionally, paired sample t-test revealed that there were significant differences in the three variables within the experimental group between before and after practicing the 12-step program. Therefore, it can be concluded that the 12-step program is one way to get back from codependency and help families to recover from this syndrome. Keywords: 12-step program, Al-Anon & Nar-Anon, Codependency, Spirituality.